Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
(x + 3)/5 - (2x - 1)/3 = 4 / * 15
3(x + 3) - 5(2x - 1) = 15 * 4
3x + 9 - 10x + 5 = 60
7x = 60 - 9 - 5
7x = 46 / : 7
x = 6 4/7
3(x + 3) - 5(2x - 1) = 15 * 4
3x + 9 - 10x + 5 = 60
7x = 60 - 9 - 5
7x = 46 / : 7
x = 6 4/7
Answer:
X= -46/7
Step-by-step explanation:
step1: left part times 15 is 3(X+3)-5(2X-1)
step2: right part times 15 is 60
step3: 3(X+3)-5(2X-1)=60
step4: 3X+9-10X+5=60
step5: -7X+14=60
step6: -7X=46
step7: X= -46/7
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.